Kegiatan Government Public Relation dalam Membangun Komunikasi dengan Dunia Pers: Studi Kasus Humas Pemerintah Kota Administrasi Jakarta Timur - Aras, Muhammad (Bina Nusantara University, 2014)
This study focuses on the communications that was built by the Public Relations (PR) in East Jakarta Administration City Government with the Press community through their roles in the administrative activities of government. The purpose of this study was to determine the PR activities of East Jakarta Administration City Government in establishing good communication with the Press as the government's partner in promoting the various activities that are beneficial to society. The research method used in this study is a case study (case study). The results showed that the role of Public Relations of East Jakarta Administration City Government in establishing good communication with the press, is done through activities, such as press conferences, press releases, and press gathering. All activities are done well, so as to create a communication and a good relationship, in any cooperation between the Press and the Government of East Jakarta, making it easier for local governments in disseminating various work programs.